Mortalidade por coinfecção doenças tropicais negligenciadas-HIV no Brasil, 2000-2023 - Silva, Taynara Lais (2024)
Introduction: Neglected tropical diseases (NTDs) are part of a group of conditions that persist worldwide despite the availability of means to prevent and control them. They are more prevalent in vulnerable populations, in contexts of poverty and with precarious socio-economic indicators. When associated with HIV/AIDS co-infection, NTDs can contribute to a worse prognosis for the general clinical condition of those affected, and can increase the risk of complications and death. Objective: To characterise the spatial distribution patterns and temporal trends of mortality due to NTD/HIV co-infection in Brazil, 2000-2023. Methods: A population-based ecological study at the national level in Brazil, with municipalities as the unit of analysis. The spatial distribution and temporal trends of deaths due to NTD co-infection and HIV/AIDS were analysed using data from death certificates (DC) in the Mortality Information System (SIM). Simple and relative frequencies were calculated, as well as crude and age- and sex-adjusted mortality rates. To identify temporal trends, average annual percentage changes (AAPC) were calculated with their respective 95% confidence intervals (CI). For spatial analysis, global and local Moran indices were calculated. Results: A total of 13,969 deaths due to NTD-HIV co-infection were identified (adjusted mean rate: 0.30/100,000 population, 95%CI 0.30;0.31), mainly due to fungal infections (12,007; 86.0%, mean rate: 0.259/100,000 population, 95%CI 0.254;0.264), followed by infections caused by protozoa (1,318; 9.4%, adjusted mean rate 0.028/100,000 population, 95%CI 0. 027;0.030), in men (10. 030, 71.8%, adjusted mean rate 0.44/100,000 inhabitants 95%CI 0.43;0.45), in the age group 30-39 years (4. 929, 35.3%, adjusted mean rate 0.70/100,000 inhabitants 95%CI 0.68;0.72) and living in the south-eastern region (5.702; 40.8%, adjusted mean rate 0.28/100,000 inhabitants 95%CI 0.27;0.29). There was a downward trend (AAPC -0.71, 95%CI -1.32;-0.10), with an increase in the population aged ≥70 years (AAPC 2.18, 95%CI 0.13;5.17). Among the regions, the North stood out, with significant growth in rates over the period. Rates higher than 0.76/100,000 inhabitants were found in the states of Goiás, Rondônia and Mato Grosso do Sul. Spatial clusters of deaths were identified mainly in the states of Goiás and Mato Grosso do Sul. Conclusions: NTD-HIV/AIDS co-infection persisted as a relevant public health problem in Brazil during the period analysed, with a decreasing temporal trend and a heterogeneous pattern of spatial distribution. As socially determined diseases, the recognition of the mortality pattern and its temporal and spatial distribution is fundamental for the qualification of health care, prevention and control interventions targeted to areas and populations at higher risk/vulnerability.